Implementasi CRM Dalam Meningkatkan Pelanggan Pada All Olshop Tanjungbalai - Annisa Sitorus; Iqbal Kamil Siregar; Sudarmin Sudarmin (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
In marketing the sale, this Tanjungbalai All Olshop does not yet have the means or system to disseminate its products. So that customers have to visit the All Olshop Tanjungbalai, this can cause customers at All Olshop Tanjungbalai to ask in advance about detailed information about the products that are sold to the All Olshop Tanjungbalai waiter even service to customers at All Olshop Tanjungbalai is less effective because of the absence of facilities which helps customers to find out whether the stock is still available or not at All Olshop Tanjungbalai. All Tanjungbalai Olshops really need improvement, namely by building a system so that they can provide good service and satisfy customer interest and make it easier for All Tanjungbalai Olshop owners to recap the reporting of goods sold. With the Customer Relationship Management (CRM) system, it is hoped that the Tanjungbalai All Olshop will find it easier to attract more customers and maintain customer interest in becoming regular customers at All Olshop Tanjungbalai.